2019
DOI: 10.22146/agritech.41736
|View full text |Cite
|
Sign up to set email alerts
|

Pola Perubahan Protein Koro Benguk (Mucuna pruriens) Selama Fermentasi Tempe Menggunakan Inokulum Raprima

Abstract: Tempe merupakan makanan sehat dikarenakan kandungan komponen bioaktif dan merupakan sumber protein bagi vegetarian. Selama proses fermentasi, jamur tempe akan menghasilkan enzim protease yang memecah protein biji menjadi peptida bioaktif. Jenis jamur tempe dan lama fermentasi akan mempengaruhi peptida bioaktif yang terbentuk. Penelitian ini bertujuan untuk mengetahui pengaruh ragi tempe Raprima terhadap perubahan konsentrasi peptida dan pola protein selama fermentasi tempe koro benguk. Hasil penelitian menunju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 9 publications
0
7
0
5
Order By: Relevance
“…The longer fermentation causes the further process of hydrolysis by molds thus increasing the short-chain peptide which results in an increasing degree of hydrolysis value. This is following Rahayu et al (2019) that the degree of hydrolysis of the swollen tempeh koro has increased sharply in the first 24 hours, the longer incubation slightly increases the degree of hydrolysis but not as sharp at the beginning of fermentation, then after 48 hours of fermentation, the percentage of hydrolyzed protein is relatively stable (around 45%). Increased papain addition can increase the degree of hydrolysis because papain from papaya latex is an endopeptidase containing 10% papain enzyme and 45% kimopapain which makes papain from papaya latex have a high hydrolytic ability.…”
Section: Degree Of Hydrolysismentioning
confidence: 70%
See 1 more Smart Citation
“…The longer fermentation causes the further process of hydrolysis by molds thus increasing the short-chain peptide which results in an increasing degree of hydrolysis value. This is following Rahayu et al (2019) that the degree of hydrolysis of the swollen tempeh koro has increased sharply in the first 24 hours, the longer incubation slightly increases the degree of hydrolysis but not as sharp at the beginning of fermentation, then after 48 hours of fermentation, the percentage of hydrolyzed protein is relatively stable (around 45%). Increased papain addition can increase the degree of hydrolysis because papain from papaya latex is an endopeptidase containing 10% papain enzyme and 45% kimopapain which makes papain from papaya latex have a high hydrolytic ability.…”
Section: Degree Of Hydrolysismentioning
confidence: 70%
“…Puteri et al, (2015); ** Witono et al, (2015) The faster the fermentation time, the lower the simple components formed. This is supported by Rahayu et al (2019) which showed that the total amount of hydrolyzed soy protein increases with the length of time of fermentation, so that total nitrogen and water-soluble amino acids increase (Puteri et al, 2018).…”
Section: Glutamic Acid Contentmentioning
confidence: 89%
“…Rhizopus sp. is a mold found in tempe yeast (Rahayu et al, 2019). This study used tempe yeast inoculum in the manufacture of VCO, and the results showed that the administration of different amounts of inoculum affected the resulting VCO because yeast acted as a fermenter for coconut milk by utilizing it as a nutrient, producing VCO yields that tended to increase with the amount of yeast.…”
Section: Treatmentmentioning
confidence: 95%
“…Not all of non-soybean materials can be modified with the same manufacturing process depends on their thickness, size and structure. The manufacture of tempeh from several types of materials has different treatment times for soaking, boiling/steaming and the length of fermentation time [6,9].…”
Section: Figure 1 Mold Viability Of Tempehmentioning
confidence: 99%